CD4+FoxP3+ regulatory T cells suppress fatal T helper 2 cell immunity during pulmonary fungal infection. Issue 12 (29th October 2014) - Schulze, Bianca; Piehler, Daniel; Eschke, Maria; von Buttlar, Heiner; Köhler, Gabriele; Sparwasser, Tim; Alber, Gottfried
Abstract : The opportunistic fungal pathogen Cryptococcus neoformans causes lung inflammation and fatal meningitis in immunocompromised patients. Regulatory T (Treg) cells play an important role in controlling immunity and homeostasis. However, their functional role during fungal infection is largely unknown. In this study, we investigated the role of Treg cells during experimental murine pulmonary C. neoformans infection. We show that the number of CD4 + FoxP3 + Treg cells in the lung increases significantly within the first 4 weeks after intranasal infection of BALB/c wild‐type mice. To define the function of Treg cells we used DEREG mice allowing selective depletion of CD4 + FoxP3 + Treg cells by application of diphtheria toxin. In Treg cell‐depleted mice, stronger pulmonary allergic inflammation with enhanced mucus production and pronounced eosinophilia, increased IgE production, and elevated fungal lung burden were found. This was accompanied by higher frequencies of GATA‐3 + T helper (Th) 2 cells with elevated capacity to produce interleukin (IL)‐4, IL‐5, and IL‐13. In contrast, only a mild increase in the Th1‐associated immune response unrelated to the fungal infection was observed. In conclusion, the data demonstrate that during fungal infection pulmonary Treg cells are induced and preferentially suppress Th2 cells thereby mediating enhanced fungal control.